2023
DOI: 10.3390/v15020547
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Glioblastoma Therapy: Oncolytic Viruses and Emerging Future Strategies

Abstract: Glioblastoma is the most aggressive form of malignant brain tumor. Standard treatment protocols and traditional immunotherapy are poorly effective as they do not significantly increase the long-term survival of glioblastoma patients. Oncolytic viruses (OVs) may be an effective alternative approach. Combining OVs with some modern treatment options may also provide significant benefits for glioblastoma patients. Here we review virotherapy for glioblastomas and describe several OVs and their combination with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 239 publications
0
21
0
Order By: Relevance
“…Thus, if SARS-CoV-2 is to be used as an oncolytic therapy vector, a series of genetically engineered modifications need to be conducted. Similar to the case of combining poliovirus and rhinovirus to form a recombinant poliovirus chimera ( 24 ), it is necessary to further attenuate pathogenicity and cytotoxicity, and enhance specificity and security if SARS-CoV-2 is to play a role in antitumor immunomodulation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if SARS-CoV-2 is to be used as an oncolytic therapy vector, a series of genetically engineered modifications need to be conducted. Similar to the case of combining poliovirus and rhinovirus to form a recombinant poliovirus chimera ( 24 ), it is necessary to further attenuate pathogenicity and cytotoxicity, and enhance specificity and security if SARS-CoV-2 is to play a role in antitumor immunomodulation.…”
Section: Discussionmentioning
confidence: 99%
“…Oncolytic virotherapy is a novel approach for the targeted therapy of neoplasms that utilizes viruses for the elimination of tumor cells. While the exact mechanisms and the nature of tropism for such viruses might still be unknown, the main theories involve either direct killing of the targeted cells or indirect modulation of the host’s immune system response in order to mediate immunogenic cytotoxicity [ 158 , 159 ]. Clinical trials that have tested oncolytic virotherapy showed increased overall survival as compared with historical controls for polio-rhinovirus chimera PVSRIPO [ 160 ]; tumor reduction and safety were observed for tumor-replicative adenovirus DNX2401 with a median overall survival at 13 months for patients who received the treatment intratumorally [ 161 ].…”
Section: Drug Delivery Systems For Active Targeting Of Brain Tumorsmentioning
confidence: 99%
“…GB is particularly suitable for viral therapy to overcome TME immunosuppression and growth being surrounded mainly by post-mitotic cells, which allows the use of viruses that require active cell cycles for replication [ 835 ]. Viruses used to treat tumors can be divided into two categories: (1) oncolytic viruses (OVs) with the natural capacity to replicate only in cancer cells (reoviruses, and Newcastle disease viruses) or that are vulnerable to genetic manipulation that increases their tumor selectivity (adenoviruses, herpes simplex viruses, vaccina viruses, polioviruses, and measles viruses); and (2) viral vectors with a low replication rate, which are used as vehicles for other therapeutic genes [ 836 ]. Any of the viral categories can stimulate an immune response without the expression of an immunomodulatory transgene.…”
Section: Immunotherapiesmentioning
confidence: 99%
“…In addition, OVs have many advantages over conventional immunotherapies, including precise targeting, effective killing rates, and minimal adverse reactions [ 858 ]. To date, several clinical trials have been carried out for oncolytic viruses to improve the treatment of GB [ 836 , 843 , 857 ]. Examples include adenovirus [ 859 , 860 , 861 ], herpes simplex virus [ 862 , 863 , 864 ], reovirus [ 865 , 866 ], parvovirus [ 867 ], measles virus [ 868 , 869 , 870 ], poliovirus [ 853 , 871 ], vaccinia virus [ 872 ] and Newcastle disease virus [ 873 ].…”
Section: Immunotherapiesmentioning
confidence: 99%